Islamic Counseling Guidance Program for Instilling Good Manners among Public Elementary School Students - Deden Herman Hermawan; Santi Lisnawati; Wido Supraha (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The cultivation of adab (Islamic manners and moral conduct) among elementary school students is a fundamental aspect of Islamic education that plays a crucial role in shaping character and personality from an early age. However, the implementation of adab development in public elementary schools has not yet been systematically integrated into educational services. This study aims to develop and examine the feasibility of an Islamic Guidance and Counseling Program as an effort to instill adab among public elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, limited implementation, and evaluation stages. Data were collected through interviews, questionnaires, and expert validation. The findings indicate that the majority of respondents strongly agreed that the Islamic Guidance and Counseling Program is highly needed to help students distinguish between good and bad behavior based on Islamic values. The results of expert validation involving material experts, Islamic moral education experts, and Islamic guidance and counseling experts showed feasibility percentages of 90% and 83.33%, categorized as very feasible. Therefore, the developed Islamic Guidance and Counseling Program is considered appropriate for use as a guideline for instilling adab among elementary school students after revisions based on expert recommendations